Comparative Analysis on Copra and Dehusked Coconut (Baker) in Magsaysay Davao del Sur - Barriga, Jency O.; Canaya, Jellie O.; Hitutuane, Michelle B.; Maslog, Honey Mae B. (--Davao del Sur; UM Bansalan College, 2018)
This study was conducted in order to find out the comparative analysis on farmers preference on selling coconut harvest and its level of productivity that needs for improvements; what possible recommendation that will help farmers for betterment of their farm; and imparting knowledge of the helpful programs offered. Based on the result presented, the researchers conducted that the preferred method used mostly in the place is copra. Aside of being the most productive, it has also been the most favorable method because of its double income opportunity.